AB0251 Are acpa associated with more bone loss over time in patients with ra?. (12th June 2018) - Amkreutz, J.A.M.P.; de Moel, E.C.; Heimans, L.; Allaart, C.F.; Huizinga, T.W.J.; van der Woude, D.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are one of the most important serological markers for rheumatoid arthritis (RA) and have been suggested to play a pathophysiologic role by directly binding to osteoclasts. However, the effect of ACPA on systemic bone mineral density (BMD) and in particular their effect on changes in BMD over time is currently unknown. Objectives: The aim of this study was to determine whether ACPA associate with changes in BMD over time in patients with RA. Methods: Yearly dual X-ray absorptiometry (DXA) scores were performed during 5 years of follow-up in 412 patients with recent-onset RA participating in the IMPROVED study 1, a clinical trial in which patients were treated according to a remission- (disease activity score <1.6) steered strategy. The effect of the presence of ACPA on 1) Z-scores of lumbar spine and hip over time, and 2) prevalence of osteopenia/osteoporosis (defined as a T-score ≤−1) over time was analysed using generalised estimating equations. Analyses were adjusted for age, gender, BMI, symptom duration, smoking status, disease activity, prednisone intake, usage of bisphosphonates, calcium intake and serum 25-OH vitamin D levels. Results: ACPA-positive patients had a significantly lower lumbar spine (p=0.04) and hip (p=0.01) Z-score at baseline. There was no difference in prevalence of osteoporosis/osteopenia at baseline between ACPA-positive and ACPA-negative patients (OR (95% CI) 1.02 (0.55 to 1.19)). We hypothesised that ACPA-positive patients would have more BMD loss over time compared to ACPA-negative patients. However, ACPA-positivity did not associate with a stronger decline in Z-score over time at lumbar (p=0.43) or femoral sites (p=0.67). Additionally, no effect of ACPA-positivity was found on the development of osteoporosis/osteopenia over time (p=0.23). Conclusions: ACPA-positive patients have a significantly lower baseline BMD compared to ACPA-negative patients. Surprisingly, ACPA do not associate with a decrease in BMD over time in patients who were treated according to a tight control strategy. These results indicate that ACPA alone do not contribute to bone loss after disease onset in the absence of inflammation/disease activity. Reference: [1] Wevers-de Boer K, et al. Ann Rheum Dis. 2012Sep;71(9):1472–7. Disclosure of Interest: None declared